Flexibly funding WHO? An analysis of its donors’ voluntary contributions - Andrew Harmer; Jonathan Kennedy; Obichukwu Iwunna (BMJ Global Health)
Introduction Since the 1970s, voluntary contributions have become an increasingly important component of WHO’s budget. As voluntary contributions tend to be earmarked for donor-specified programmes and projects, there are concerns that this trend has diverted focus away from WHO’s strategic priorities, made coordination and attaining coherence more difficult, undermined WHO’s democratic structures and given undue power to a handful of wealthy donors. In the past few years, the WHO Secretariat has pushed for donors to increase the amount of flexible funding they provide.Methods This paper aims to add to the literature on WHO financing by constructing and analysing a dataset based on figures extracted from WHO documents for the period 2010–21. It aims to answer two questions: who funds WHO and how flexible is that funding?Results Our analysis demonstrates that in the last decade voluntary contributions have steadily increased as a proportion of WHO’s budget, from 75% at the start of the period to 88% at the end. High-income countries and donors based in high-income countries provided 90% of voluntary contributions in 2020. Surprisingly, the share of voluntary contributions provided by upper middle-income countries was consistently less than the share by lower middle-income countries. Furthermore, in terms of their share of voluntary contributions, we found that upper middle-income countries contributed the least proportion of their gross national income to WHO.Conclusion We conclude that WHO remains constrained by the conditions attached to the vast majority of funding that it receives from its donors. Further work on how to flexibly fund WHO is required. We recommend that the Agile Member States Task Group on Strengthening WHO’s Budgetary, Programmatic and Financing Governance continues the work of the Working Group on Sustainable Financing by focusing on the incentives that determine donor support for specified and flexible voluntary contributions.